Exchange-rate strategies in developing countries - Renate Ohr (Intereconomics, 1991)
Exchange-rate strategies may be used to pursue the most varied objectives as instruments of development policy or of structural adjustment. The following article will examine the advantages and disadvantages of a number of exchange-rate policy options.
Keywords: 330; Development Strategy